2015
DOI: 10.1037/adb0000063
|View full text |Cite
|
Sign up to set email alerts
|

Examining temptation to drink from an existential perspective: Associations among temptation, purpose in life, and drinking outcomes.

Abstract: Temptation to drink, defined as the degree to which one feels compelled to drink in the presence of internal or external alcohol-related cues, has been shown to predict alcohol treatment outcomes among individuals with alcohol use disorders (AUDs). Research examining temptation to drink from an existential perspective is lacking and little is known about how existential issues such as purpose in life (PIL) relate to temptation to drink, which is surprising given the role of existential issues in many treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 51 publications
2
20
0
1
Order By: Relevance
“…Finally, Minehan and colleagues (2000) determined that higher purpose in life predicted less alcohol use and that higher existential anxiety was associated with increased rates of illicit drug use. These findings are consistent with research conducted on adults where substance use is associated with living a life devoid of meaning and purpose (Marsh, Smith, Piek, & Saunders, 2003; Martin, MacKinnon, Johnson, & Rohsenow, 2011; Roos, Kirouac, Pearson, Fink, & Witkiewitz, 2015; Thompson, 2012; Wiklund, 2008). Testimonies of individuals who abuse substances frequently describe a monotonous, boring, hollow, and empty existence (Kemp, 2009b, 2011; Kemp & Butler, 2014; Thompson, 2012).…”
Section: Core Elements Of Lived Experience In Relation To Adolescent ...supporting
confidence: 90%
“…Finally, Minehan and colleagues (2000) determined that higher purpose in life predicted less alcohol use and that higher existential anxiety was associated with increased rates of illicit drug use. These findings are consistent with research conducted on adults where substance use is associated with living a life devoid of meaning and purpose (Marsh, Smith, Piek, & Saunders, 2003; Martin, MacKinnon, Johnson, & Rohsenow, 2011; Roos, Kirouac, Pearson, Fink, & Witkiewitz, 2015; Thompson, 2012; Wiklund, 2008). Testimonies of individuals who abuse substances frequently describe a monotonous, boring, hollow, and empty existence (Kemp, 2009b, 2011; Kemp & Butler, 2014; Thompson, 2012).…”
Section: Core Elements Of Lived Experience In Relation To Adolescent ...supporting
confidence: 90%
“…Studies suggest that meditation practice is associated with increases in values clarification and purpose and that values clarification is associated with positive psychological states and sense of control [124, 125]. Furthermore, observational studies demonstrated that higher values clarification levels were associated with lower temptation to drink alcohol and lower drinking frequency and drinking-related consequences [126], and that values clarification mediated associations between dispositional mindfulness and alcohol-related problems [127]. …”
Section: Self-awarenessmentioning
confidence: 99%
“…Many predictors of recovery outcomes have been studied. Individuals who are married, female, and older [10], with fewer heavy drinkers in their social network [11], greater coping skills [12], fewer psychiatric disorders [10], lower levels of depression and anger [13,14], higher levels of purpose in life and Alcoholics Anonymous (AA) attendance [15,16], and a higher level of abstinence self-efficacy [17,18] tend to have better outcomes following treatment. Higher alcohol dependence severity is associated with an increased odds of an abstinent recovery (defined as abstinence from alcohol and remission from alcohol dependence symptoms), but decreased odds of a non-abstinent recovery (defined as low risk drinking and remission from alcohol dependence symptoms) [19].…”
Section: Introductionmentioning
confidence: 99%